2016
DOI: 10.1007/s00125-016-4013-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetic retinopathy in screening-detected diabetes mellitus: results from the Gutenberg Health Study (GHS)

Abstract: Aims/hypothesis Individuals with type 2 diabetes mellitus may experience an asymptomatic period of hyperglycaemia, and complications may already be present at the time of diagnosis. We aimed to determine the prevalence of diabetic retinopathy in patients with newly diagnosed (screeningdetected) type 2 diabetes. Methods The Gutenberg Health Study is a population-based study with 15,010 participants aged between 35 and 74 years. We determined the weighted prevalence of diabetic retinopathy by assessing fundus ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 37 publications
2
38
0
5
Order By: Relevance
“…Diabetic retinopathy ranks fifth among common causes for blindness or severe vision impairment and a recent meta-analysis revealed that the age-standardised prevalence of diabetic retinopathyrelated blindness will increase due to increasing populations and average age together with a reduction in death rates [2]. Lending support to the magnitude of the problem are reports that even when a person first presents at screening services, advanced diabetic retinopathy is present at levels that are no longer amenable to medical interventions [3,4]. Recent population-based studies from Europe revealed that screening-detected diabetic retinopathy appeared in more than…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic retinopathy ranks fifth among common causes for blindness or severe vision impairment and a recent meta-analysis revealed that the age-standardised prevalence of diabetic retinopathyrelated blindness will increase due to increasing populations and average age together with a reduction in death rates [2]. Lending support to the magnitude of the problem are reports that even when a person first presents at screening services, advanced diabetic retinopathy is present at levels that are no longer amenable to medical interventions [3,4]. Recent population-based studies from Europe revealed that screening-detected diabetic retinopathy appeared in more than…”
mentioning
confidence: 99%
“…13% of individuals with newly diagnosed type 2 diabetes [4]. Although lower than the rate reported from the UK Prospective Diabetes Study (UKPDS) [5], diabetes is still underdiagnosed and individuals may present when retinopathy is beyond the 'point of no return' at which progression can be halted by glucose-lowering therapy (see Fig.…”
mentioning
confidence: 99%
“…To the Editor: Ponto and colleagues would have us believe that 12.6% of type 2 diabetic patients newly diagnosed through a screening programme of the general population had retinopathy at the time of diagnosis [1]. This is not the case.…”
Section: Etdrs Early Treatment Diabetic Retinopathy Studymentioning
confidence: 99%
“…Those criteria for mild diabetic retinopathy are 'at least one microaneurysm, and definition not met for moderate nonproliferative retinopathy, severe nonproliferative retinopathy, early proliferative retinopathy, or high-risk proliferative retinopathy' [2]. Of the patients who screened positive for diabetes, 11.6% had mild diabetic retinopathy by these criteria [1]. It turns out that 5-10% of the general population without diabetes or hypertension have signs of isolated retinopathy that meet the ETDRS criteria for 'mild' diabetic retinopathy.…”
Section: Etdrs Early Treatment Diabetic Retinopathy Studymentioning
confidence: 99%
“…Ohguro i saradnici (20) navode poboljšanje oštrine vida nakon retrobulbarne injekcije TA. U našoj studiji je uočena statistički značajna razlika oštrine vida pre i dva meseca nakon terapije zadnjom suptenonskom injekcijom TA -oštrina vida se značajno poboljšala nakon tretmana, što je u skladu sa nalazima obe navedene studije.…”
Section: Diskusijaunclassified